2014
DOI: 10.3109/07420528.2014.980508
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chronotype and intelligence on academic achievement in primary school is mediated by conscientiousness, midpoint of sleep and motivation

Abstract: Individuals differ in their timing of sleep (bed times, rise times) and in their preference for morning or evening hours. Previous work focused on the relationship between academic achievement and these variables in secondary school students. The main aim of the study is to investigate the relationship between chronotype and academic achievement in 10-year-old children (n = 1125) attending 4th grade of primary school. They filled a cognitive test (Culture Fair Intelligence Test, CFT 20-R) and questions about r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 60 publications
2
55
2
Order By: Relevance
“…A possible explanation of the small observed effect sizes is that circadian preference does not represent the most relevant component explaining the academic achievement. Other important predictors of academic achievement are intelligence/ cognitive ability (Rindermann & Neubauer, 2004;Spinath et al, 2006), conscientiousness (Furnham et al, 2002;Steinmayr & Spinath, 2008) and motivation (Roeser et al, 2013), but to date, no study has assessed these variables together with circadian preference (Arbabi et al, 2015). Nevertheless, in the case of low academic achievement, an intervention which takes into account also a not so preponderant factor as circadian preference, could reach anyway significant outcomes (see ''practical implications'' sub-paragraph).…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation of the small observed effect sizes is that circadian preference does not represent the most relevant component explaining the academic achievement. Other important predictors of academic achievement are intelligence/ cognitive ability (Rindermann & Neubauer, 2004;Spinath et al, 2006), conscientiousness (Furnham et al, 2002;Steinmayr & Spinath, 2008) and motivation (Roeser et al, 2013), but to date, no study has assessed these variables together with circadian preference (Arbabi et al, 2015). Nevertheless, in the case of low academic achievement, an intervention which takes into account also a not so preponderant factor as circadian preference, could reach anyway significant outcomes (see ''practical implications'' sub-paragraph).…”
Section: Discussionmentioning
confidence: 97%
“…More recently, of the studies performed on the association between circadian preference and school performance in adolescents, the majority [9,[15][16][17][18][19][20] showed a negative association between eveningness and school performance, while only three failed to show this relationship [21][22][23]. Nevertheless, it should be noted that circadian preference has also been related to intelligence [1], with eveningness being associated with higher intelligence scores in most studies [24][25][26][27], while only one study reported the opposite relationship [28]. This set of results could potentially explain the partial disagreement among studies that have recently explored the relationship between circadian preference and school performance in adolescents [9,[15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 94%
“…Importantly, early and late chronotypes in our study performed equally well in the afternoon. A number of reports have purported that either early or late chronotypes are more or less intelligent 1113 . Based on the lack of agreement between these studies, their weak significance, and our previous findings, we assume that chronotype is not associated with intelligence.…”
Section: Introductionmentioning
confidence: 99%